Colonial And Hybrid Desire: A Postcolonial Reading of Translations by Brian Friel - Atheer Makki Abd Ali AlJasim (Genius Journals, 2023)
European countries imposed their dominance on other communities and cultures, and the aftereffects of colonialism need to be discussed in the context of the postmodern era. To that end, this presentation will examine Brian Friel's Translations from a postcolonial perspective. This research proposes a postcolonial reading of Translations, focusing on the story's characters and central ideas. Lieutenant Yolland, Maire, Owen, and Captain Lancey illustrate Western imperialism's devastating nature. The study will focus solely on the play's use of postcolonial ideas, as defined by Homi K. Bhabha and Gramsci's appropriation, hybridity, imitation, hegemony, and exoticism.
Keywords: Postcolonialism; appropriation; hybridity; mimicry